CONDITION REGARDING PROTECTION BY INDICATIVE SIGNS - Adrian CURELEA (Challenges of the Knowledge Society)
The study aims to highlight the conditions that a product must meet in order to be protected by an indicative sign as well as the advantages conferred by means of protection through the prism of Community legislation and the CJEU jurisprudence. Indicative signs are marketing tools that contribute to the effective promotion of the product protected by a European and national quality system, intended to protect consumers against misleading practices aimed at misleading them about the geographical origin or production methods of the product, as well as producers against acts of unfair competition. Geographical indications, designations of origin and names of guaranteed traditional specialties allow consumers to trust and distinguish quality products, also helping producers in their marketing, in the case of the former, the connection between the specific geographical region and the name of the product being highlighted, in case a certain quality, reputation or other characteristic can be attributed essentially or exclusively to its geographical origin, as regards traditional specialties guaranteed, the link referring to the production method used over time in the determined geographical region with the quality and characteristics of the product protected by indicative sign. The protection of indicative signs is an effective tool to prevent the use of a name on the market, but this protection does not aim to limit the range of products available on the market, but to reserve a specific name for products that comply with the requirements of the specifications and that have a link clear geographical connection with a certain place, region or, as we have seen, in some cases, with the territory of a country, which does not prevent other producers from marketing the same type of product under a different name. It is unanimously accepted that the added value conferred by the indicative signs is based on the trust of consumers and only an effective protection system can guarantee them that a certain quality, characteristic or reputation of the products protected by the indicative sign are maintained for the entire duration of the protection period.